New approach towards imaging lambda-DNA using scanning tunneling microscopy/spectroscopy (STM/STS) - Dey, Shirshendu; Pethkar, Sushama; Adyanthaya, Suguna D.; Sastry, Murali; Dharmadhikari, C. V. (Bulletin of Materials Science, 2008)
A new methodology to anchor A-DNA to silanized n-Si(111) surface using Langmuir Blodget trough was developed. The n-Si (111) was silanized by treating it with low molecular weight octyltrichlorosilane in toluene. Scanning tunneling microscopy (STM) image of lambda-DNA on octyltrichlorosilane deposited Si substrate shows areas exhibiting arrayed structures of 700 nm length and 40 nm spacing. Scanning tunneling spectroscopy (STS) at different stages depict a broad distribution of defect states in the bandgap region of n-Si(111) which presumably facilitates tunneling through otherwise insulating DNA layer.
Keywords: DNA; Langmuir Blodget technique; Scanning tunneling microscopy; silanization

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Strong electric field modulation of transport in PVDF/MWCNT nanocomposite near the percolation threshold - Chanmal, Chetan; Deo, Meenal S.; Rana, Abhimanyu; Jog, Jyoti Prakash; Ogale, Satishchandra B. (Solid State Communications, 2011)
A nanocomposite comprising of multiwalled carbon nanotubes (MWCNT) embedded in ferroelectric Poly(vinylidene fluoride) PVDF polymer matrix is examined for electric field induced transport modulation. The pulsed laser deposition (PLD) grown thin films of the nanocomposite with different MWCNT content were characterized. When used as a channel layer in a field effect transistor configuration, a strong electric field modulation of the transport was realized just below the percolation threshold. We believe that this nanocomposite non-percolating channel concept can provide several opportunities for FET devices for organic electronics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Field effect device; pulsed laser deposition; PVDF; Scanning tunneling microscopy

Investigation of disorder in mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon - Patil, Sumati; Kolekar, Sadhu; Kumar, Arvind; Alegaonkar, Prashant; Datar, Suwarna; Dharmadhikari, C. V. (Journal of Nanoscience and Nanotechnology, 2018)
Disorder in a mixed phase, sp(2)-sp(3) bonded graphene-like nanocarbon (GNC) lattice has been extensively studied for its electronic and field emission properties. Morphological investigations are performed using scanning electron microscopy (SEM) which depicts microstructures comprising of atomically flat terraces (c-planes) with an abundance of edges (ab planes which are orthogonal to c-planes). Scanning tunneling microscopy (STM) is used to observe the atomic structure of basal planes whereas field emission microscopy (FEM) is found to be suitable for resolving nanotopography of edges. STM images revealed the hexagonal and non-hexagonal atomic arrangements in addition to a variety of defect structures. Scanning tunneling spectroscopy is carried out to study the effect of this short-range disorder on the local density of states. Current versus voltage (I-V) characteristics have been recorded at different defect sites and are compared with respect to the extent of the defect. As sharp edges of GNC are expected to be excellent field emitters, because of low work function and high electric field, enhancement in current is observed particularly when applied electric field is along basal planes. Therefore, it is worthwhile to investigate field emission from these samples. The FEM images show a cluster of bright spots at low voltages which later transformed into an array resembling ledges of ab-planes with increasing voltage. Reproducible I-V curves yield linear Fowler-Nordheim plots supporting field emission as the dominant mechanism of electron emission. Turn on field for 10 mu A current is estimated to be similar to 3 V/mu m.
Keywords: Field emission microscopy; Graphene-Like Nanocarbon; Scanning tunneling microscopy; Scanning Tunneling Spectroscopy

Scanning tunneling microscopy investigation of synaptic behavior in AgInS2 quantum dots: effect of ion transport in neuromorphic applications - Betal, Atanu; Chetia, Anupam; Bera, Jayanta; Saikia, Dibyajyoti; Sharma, Ashish; Rath, Arup K.; Sahu, Satyajit (ACS Applied Nano Materials, 2024)
Scanning tunneling microscopy (STM) is a powerful technique for investigating the nanoscale properties of functional materials. Additionally, scanning tunneling spectroscopy (STS) facilitates the determination of the local density of states (LDOS) within the material. In this study, we present an exploration of the resistive switching (RS) properties and neuromorphic computing capabilities of individual AgInS2 quantum dots, utilizing STM and STS techniques. By examining the material's bandgap and its temperature dependence, we uncover a nonlinear variation below the Debye temperature and a linear trend at higher temperatures. Moreover, STS measurements demonstrate changes in the conducting states induced by localized pulses, further confirming the unique characteristics of the quantum dots. The experimental devices constructed by using these quantum dots effectively replicate the RS properties observed at the nanoscale. To assess the neuromorphic application of the devices, pulse transient measurements simulating the learning and forgetting processes were conducted. The gradual set and reset processes successfully mimic the information retention and erasure capabilities essential for neuromorphic computing. Notably, the resistive switching mechanism in these devices is attributed to localized ionic transport, which highlights the significant involvement of ionic species in the observed RS behavior. The outcomes of this study contribute to the fundamental understanding of RS properties in single AgInS2 quantum dots and offer valuable insights into their potential applications in neuromorphic computing.
Keywords: corona poling; Ion transport; neuromorphic computing; quantum dots; resistive switching; Scanning tunneling microscopy; STS